INNV-15. PROTEIN TYPING AND MRNA ANALYSIS OF CIRCULATING EXOSOMES FOR GLIOBLASTOMA THERAPY USING PLASMONIC-ENHANCED INTEGRATED MAGNETO-ELECTROCHEMICAL SENSOR. (12th November 2021) - Lin, Hsing-Ying; Huang, Chen-Han; Hsu, Peng-Wei; Lu, Yu-Jen; Chou, Peter C Y; Chen, Hugo C H; Liu, Vicky Y H
Abstract: Monitoring of drug efficacy in glioblastoma multiforme (GBM) is a major clinical problem. Glioblastomas shed large quantities of exosomes into the circulation. Although these hold promise as potential biomarkers of therapeutic response, their identification and quantification remain challenging. Recently, we develop a highly sensitive and rapid analytical technique for profiling circulating exosomes directly from serum plasma of patients with glioblastoma. Exosomes are labeled with target-specific metal nanoparticles and detected by a miniaturized integrated magneto-electrochemical sensing system. Compared with current methods, this integrated system has a much higher detection sensitivity and can differentiate GBM exosomes from nontumor host cell–derived exosomes. We also show that circulating GBM exosomes can be used to analyze primary tumor mutations and as a predictive metric of treatment-induced changes. This platform could provide both an early indicator of drug efficacy and a potential molecular stratifier for human clinical trials.